Electric field-induced strain response of lead-free Fe2O3 nanoparticles-modified Bi0.5(Na0.80K0.20)0.5TiO3-0.03(Ba0.70Sr0.03)TiO3 piezoelectric ceramics - Jaita P. (2017)
© 2017 Elsevier Ltd and Techna Group S.r.l. In this research, the effects of Fe 2 O 3 nanoparticles additive on the phase evolution, dielectric, ferroelectric, piezoelectric and electric field-induced strain responses of BNKT-based piezoelectric ceramics were systematically investigated. The Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 -0.03(Ba 0.70 Sr 0.03 )TiO 3 or BNKT-0.03BSrT piezoelectric ceramics with the addition of 0–2 vol% Fe 2 O 3 nanoparticles were prepared by a solid-state reaction method. Optimum sintering temperature was found to be 1125 °C for 2 h at which all compositions had high densities of 5.73–5.80 g/cm 3 . All compositions exhibited a perovskite structure with no impurity. The XRD result showed coexisting rhombohedral and tetragonal phases throughout the entire compositional range with the rhombohedral phase becoming dominant at higher Fe 2 O 3 content. The addition of Fe 2 O 3 promoted the diffuse phase transition in the system that is characteristic of a relaxor-like mechanism and interrupted the polarization which leads to a reduction in the remanent polarization and coercive field. However, the destabilization of the ferroelectric order is accompanied by a significant increase in electric field-induced strain response for the studied system. A large electric field-induced strains (S max ) of 0.38% and a normalized strain coefficient (d * 33 = S max /E max ) of 760 pm/V were obtained for the 1 vol% Fe 2 O 3 ceramic. The obtained results indicate that the addition of Fe 2 O 3 significantly enhances the field-induced strain in BNKT-0.03BST ceramics, and the studied material is considered as a promising candidate for lead-free electromechanical actuator applications.